5+(4-1)(3)=

Simple and best practice solution for 5+(4-1)(3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+(4-1)(3)= equation:


Simplifying
5 + (4 + -1)(3) = 0

Combine like terms: 4 + -1 = 3
5 + (3)(3) = 0

Multiply 3 * 3
5 + 9 = 0

Combine like terms: 5 + 9 = 14
14 = 0

Solving
14 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7x+4-2x=10 | | 8x-(6x+8)=3x-41 | | 5(-2x-4)-3(4x+5)=9 | | 4x+4=2(3+2x) | | 2=-(p+4) | | 12+(10-1)(3)= | | 12+(1-1)(3)= | | 49x^2+14+1=0 | | 12+(4-1)(3)= | | (S+9)=8 | | 12+(n-1)(3)= | | 3x=-4x+42 | | -540+13.50x=150 | | 5x+2=2.4 | | 3n^2-15n=3n^2+n-18n-5 | | -8+7r=-8(1-4r) | | 3,615.50+(255)=x | | 14s-9s=(5) | | 6m=5n | | 4x^2+12x=9400 | | (11)r-(13)r-(11)=9 | | 4x-20=-3x-15 | | 7n-5=3n+3 | | 6(x-3)=6x-3 | | -2(n-2)+4=62 | | (4)v-(3)v+9=17 | | 3t-3=29-t | | (x+2)2+(y+3)2=196 | | 1.94x-1.25x+4.32=0.4(1.15x+8.5) | | 42x^2-21x+7=0 | | 5d-2d-3=3 | | 3t-3=29-3 |

Equations solver categories